Effect of putrescine on growth and productivity of wheat under water stress conditions - Meena, Pinkey; Solanki, N.S.; L.N. Dashora, L.N. (Annals of Agricultural Research, 2016)
A field experiment was conducted at Rajasthan College of Agriculture, Udaipur, Rajasthan during rabi 2013-14 to assess the effect of putrescine in mitigating the water stress in wheat. The experiment consisted of 4 water stress conditions (no water stress, water stress at tillering stage, heading stage and both tillering + heading stage ) and 4 rates of putrescine spray viz., control (water spray), 10 ppm, 50 ppm and 100 ppm. Treatments were evaluated using split-plot design allocating water stress treatments in main- plots and foliar spray of putrescine in sub-plots with four replication. Water stress at tillering, heading and tillering + heading stages caused significant reduction in grain yield, the magnitude of reduction being 4.0, 11.3 and 16.8 %, respectively over no water stress. No water stress treatment recorded the highest net returns (` 91484ha-1) and B:C ratio (3.1). Proline content increased while Relative Water Content (RWC) and chlorophyll content decreased under water stress treatments as compared to no water stress treatments. Foliar spray of putrescine 50 ppm resulted in significantly higher grain (5712 kg ha-1), straw (8672 kg ha-1) and biological (14384 kg ha-1) yields that were found at par with foliar spray of 100 ppm putrescine. Foliar spray of putrescine fetched lower net returns and B:C ratio as compared to water spray. However, foliar spray of 50 ppm and 100 ppm putrescine significantly increased proline content, RWC, chlorophyll content, over foliar spray of putrescine 10 ppm and water spray.